2014
DOI: 10.1002/fsn3.144
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferia parviflora extract increases energy consumption through activation of BAT in mice

Abstract: Kaempferia parviflora (KP) is a member of the ginger family and is known in Thailand as Thai ginseng, Krachai Dam or Black Ginger. TheK. parviflora extract (KPE) was previously reported to have a number of physiological effects; however, the antiobesity effects of KPE and its mechanisms remain to be elucidated. In this study, we conducted KPE feeding experiments (low dose: 0.5% KPE, high dose: 1.0% KPE) in mice to examine the antiobesity effects. For both 0.5% KPE and 1.0% KPE, 7 weeks’ feeding of KPE containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…As KP showed no notable effects on food intake, the observed anti-obesity effects may be attributable to increased EE. mice (20). We also confi rmed that intraduodenal administration of a KP extract increased sympathetic nerve activity in BAT of rats (unpublished observations).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…As KP showed no notable effects on food intake, the observed anti-obesity effects may be attributable to increased EE. mice (20). We also confi rmed that intraduodenal administration of a KP extract increased sympathetic nerve activity in BAT of rats (unpublished observations).…”
supporting
confidence: 63%
“…An anti-obesity effect of dietary supplementation of KP was reported in obese type II diabetic mice (18,19) and also in mice fed on a high-fat diet (20). As KP showed no notable effects on food intake, the observed anti-obesity effects may be attributable to increased EE.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, ingestion of KPE did not result in a change in energy intake during the ingestion period, which suggests that the anti-obesity effects of KPE involve acceleration of energy expenditure rather than inhibition of energy intake. Indeed, we previously reported that KPE enhances energy expenditure in mice via activation of sympathetic nerve activity 23. Others reported that one intake of KPE increases whole-body energy expenditure in humans 24.…”
Section: Discussionmentioning
confidence: 92%
“…KP also reportedly exhibits beneficial activities, such as anticholinesterase,11 antiinflammatory,1214 spasmolytic,15 gastric ulcer amelioration,16 antioxidative,17 and vasodilatory18 effects in addition to regulation of adipocyte differentiation 19,20. Dietary supplementation with KP extract (KPE) also reportedly suppresses body weight increases, body fat accumulation, and glucose intolerance in obese mice 2123. Other reports suggest that oral intake of KPE increases energy expenditure and fat utilization 23–25.…”
Section: Introductionmentioning
confidence: 99%